2014
DOI: 10.1111/jgs.13185
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Admission After Emergency Department Discharge in Older Adults

Abstract: Objectives To identify predictors of hospital inpatient admission of older Medicare patients following discharge from the emergency department. Design Retrospective cohort study Setting 284 non-federal California hospitals Participants 505,315 visits of patients age >65 years (yrs) with Medicare insurance discharged from California EDs in 2007. Measurement Using the California Office of Statewide Health Planning and Development files, predictors of a hospital inpatient admission within 7 days of ED dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 39 publications
(50 reference statements)
5
27
0
Order By: Relevance
“…Our findings also replicate previous reports that those who identify as Hispanic have decreased odds of inpatient admission soon after a treat-and-release ED visit [20]. …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings also replicate previous reports that those who identify as Hispanic have decreased odds of inpatient admission soon after a treat-and-release ED visit [20]. …”
Section: Discussionsupporting
confidence: 90%
“…Our inpatient admission rate after injury of 3.9% within 9 days and 7.8% within 30 days is similar to the inpatient admission rate within 7 days of 4.6% after all causes ED visits in older adults in California [20]. Unlike Gabayan et al, however, we did not find that older age was a risk factor, perhaps because we adjusted for the number of chronic comorbidities, which is closely associated with increasing age.…”
Section: Discussionsupporting
confidence: 77%
“…A diagnosis of mental illness includes dementia, mood disorders, depression, and substance-related disorders. Although this is a different study with a different population, our finding in this study are similar to our prior work in that we found cognitive impairment 43 and chronic medical conditions 44 to be associated with a poor outcome after ED discharge in older adults. Patients with mental illness possibly have a diagnosis masked by the mental illness or are suffering an impairment in mental judgment and are unable to follow ED after care instructions.…”
Section: Discussionsupporting
confidence: 88%
“…In accordance with previous literature 2,4,5 and clinical judgment, we then matched all case patients to eligible controls 1:1, using a daisy cluster algorithm that allows all variable types to be matched, not just numeric variables, 10 without replacement according to the following parameters: age, sex, Emergency Severity Index 11 score, Charlson comorbidity index score, 12 and discharge diagnosis. Sex, Emergency Severity Index score, and discharge diagnosis were perfect matches.…”
Section: Methodsmentioning
confidence: 99%